Computation validation on lateral jet interactions at supersonic speeds. (1st January 2013) - Gnemmi, Patrick; Gruhn, Patrick; Leplat, Michel; Nottin, Christophe; Wallin, Stefan
The objectives of the present Action Group AD/AG-48 of the 'Group for Aeronautical Research and Technology in EURope' (GARTEUR) on 'Lateral jet interactions at supersonic speeds' is to deeply analyse the effects of the hot-gas jet by the use of CFD simulations. At the end, the main goal is to define the most appropriate similarity parameters for wind-tunnel tests using cold gases. Experiments from DLR Cologne and ONERA/MBDA-France on generic missile models are used in order to achieve numerical simulations of the interaction between a lateral jet and a supersonic cross flow of a missile. These experiments using either a cold-air jet or a hot-gas jet, the latter produced by the combustion of a solid propellant, are well documented and the data are used for the validation of the numerical simulation using either an ideal gas or a multi-species fluid, respectively. The objective of the present work is only the validation of the numerical simulations by comparison with the DLR and ONERA/MBDA-France experiments. The action group members use the same computational meshes for the comparison of the numerical results got from different CFD codes solving 3D, turbulent, RANS equations.